Regional heterogeneity and age-related change in sub-regions of internal capsule evaluated by diffusion tensor imaging - Kawaguchi, Hiroshi; Obata, Takayuki; Ota, Miho; Akine, Yoshihide; Ito, Hiroshi; Ikehira, Hiroo; Kanno, Iwao; Suhara, Tetsuya (Brain research, 2010)
The internal capsule (IC) includes various fiber tracts supporting sensory, motor and cognitive abilities. Diffusion tensor imaging (DTI) is useful for the diagnosis of brain diseases related to IC. However, there is some risk of misdiagnosis when measuring diffusion parameters throughout the whole IC without knowledge of age-related changes, as the thin structure and branching in multiple directions must be expected to produce sub-regional differences. In this study, regional heterogeneity and age-related changes in water diffusion parameters were evaluated in sub-regions of IC. The IC region-of-interest (ROI) was first thinned to reduce contamination from surrounding tissues and then morphologically divided into three regions: anterior limb (AL), genu and posterior limb (PL). To address the branching of PL, a procedure was applied to divide the thinned PL ROI into 10 equally-spaced positions. Estimates of fractional anisotropy (FA), mean diffusivity (MD), and longitudinal (λ L) and transversal (λ T) eigenvalues showed age-related and location-dependent variation in AL, genu and PL ROIs and at the 10 equally-spaced positions of PL. Simultaneous decrease of λ L and increase of λ T resulting in decrease of FA and steady MD with aging were observed. This might be caused by age-related atrophy of main fibers such as the pyramidal tract, possibly resulting in an increase in the relative signal contribution of some crossing fibers in each pixel. Evaluation using eigenvalues (λ L and λ T), as well as FA and MD, may provide important information towards understanding age-related changes and may also be useful for clinical diagnosis of diseased IC. ►VBM in internal capsule may produce incorrect results due to partial volume effect. ►Partial volume effect can be reduced by a procedure to thin the individual ROIs. ►Diffusion parameters show sub-regional age-related changes in internal capsule. ►Age-related changes in eigenvalues suggest directional dependency of tract atrophy.